Lung ultrasound can predict heart failure developing and mortality during hospitalization in ST-segment elevation myocardial infarction. (14th October 2021) - Carreras-Mora, J; Simon-Ramon, C; Vidal-Burdeus, M; Rodriguez-Sotelo, L; Rivas-Lasarte, M; Giralt-Borrell, T; Izquierdo-Marquisa, A; Farre-Lopez, N; Marrugat-De La Iglesia, J; Sionis, A; Ribas-Barquet, N; Vaquerizo-Montilla, B; et al.
Abstract: Introduction: About 10% of patients admitted for ST-segment elevation myocardial infarction (STEMI) present with signs of heart failure at admission. Heart failure developed during hospitalization and mortality are uncommon complications in patients admitted for STEMI with no signs of heart failure at admission (Killip-Kimball class I, KKI). Most of these patients have a good prognosis during hospitalization. B-lines in lung ultrasound (LUS) provide useful diagnostic and prognostic information in heart failure patients with the potential to stratify the risk of complications in patients presenting with STEMI KKI. Purpose: To evaluate the predictive value of the LUS to develop heart failure and death during hospitalization in patients admitted with STEMI KKI. Methods: This is a prospective observational multicenter study. Consecutive patients admitted for STEMI KKI in two tertiary hospitals were included. Exclusion criteria were patients with cardiac arrest at presentation, severe lung disease or hemodialysis. The LUS was carried out by an independent operator blinded to clinical data in the first 24 hours after admission. We counted B-lines using 8-scan site LUS protocol and divided patients in two groups: wet lung group (3 or more B-lines in at least one zone) and dry lung (no positive zone). The primary endpoint was a composite of clinical congestive heart failure, cardiogenic shock or mortality during the index hospitalization. Results: From June 2020 to February 2021, 135 patients STEMI KKI patients were included. Twenty-nine patients (21, 5%) had a wet lung according to the LUS. Ten patients (7, 4%) presented the primary outcome (all of them developed heart failure, 1 of them cardiogenic shock and 2 of them died during hospitalization). Eight in 29 wet-lung patients (27, 6%) presented the primary outcome whereas only 2 in 106 (1, 9%) of the dry-lung patients [relative risk of 14, 6 (IC 95% 3, 3–65, 1)]. Patients who develop the primary outcome had no differences in NTproBNP at admission but had higher NTproBNP peak, higher troponin T peak, lower left ventricular ejection fraction and longer length of stay (Figure 1). Conclusions: In patients admitted with STEMI KKI, presenting 3 or more B-lines at least at one lung zone in the LUS at first 24 hours after admission was strongly associated with worse prognosis during hospitalization. LUS allows a better risk classification of patients and may potentially discriminate those with potential risk of complications during hospitalization from those with an excellent prognosis who can benefit from early discharge. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): 2020 grant for training and research of the Association of Ischemic Heart Disease and Critical Cardiological Care, Spanish Society of Cardiology